Workspace Enveloping Area Analysis of 5-DOF Manipulator with Link Offset - Li Fei; Wang Jie; Zhou Zhiyuan; Jiang Wei; Liu Yawen; Li Hongjun (Jixie chuandong)
The Monte Carlo method based on the kinematics positive solution is difficult to obtain the boundary feature when solving the manipulator workspace,furthermore,the shape of the workspace and the cavity of the manipulator with link offset are not obvious. The workspace boundary analysis method based on the link length and joint angle range is proposed for solving this problem. The expression of the inner and outer boundary curves of the workspace of the offset manipulator is obtained,and an intuitive and accurate workspace perspective is drawn. Based on the theoretical analysis and simulation of the two methods,the correctness of the kinematics positive solution and the Monte Carlo method is verified,and can visually see that there is a surface envelope in the workspace which is not included in the cavity. The analysis of the volume and the performance of the unpacked cavities and workspace proves that the manipulator with link offset has good workspace performance. These studies has theoretical significance and practical application value for the study on the workspace of the offset manipulator.